Variability of PRDM9 in buffaloes - Santana, Luca Godoi Rocha; Alves, Jackeline Santos; Feitosa, Fabieli Loise Braga; Rocha, Victoria Camilla Parente; Tonhati, Humberto; Costa, Raphael Bermal; de Camargo, Gregório Miguel Ferreira (Frontiers in Genetics, 2025)
The buffalo population raised in Brazil tend to show loss of genetic variability over generations, with significant estimates of inbreeding depression. Besides mating genetically distant individuals, other tools can be used to maintain/increase the genetic variability of the population, such as the use of PRDM9 genotypes. The PRDM9 gene promotes the creation of crossing-over points across the genome, with each allele promoting the creation of a different hotspot. Thus, increasing the frequency of less frequent alleles in the population, allows the emergence of new haplotypes and increases genetic variability. So, this study aimed to characterize the alleles of the PRDM9 gene circulating in the Murrah, Jaffarabadi, and Mediterranean breeds and verify their potential impact on genetic diversity management within the populations. The three alleles (B, C and D) were found in the three breeds at different frequencies, as well as the genotypic frequencies. The mating of different homozygous genotypes and genotypes carrying less frequent alleles may increase recombination rates and population variability. Four described variants and one new variant for allele D were found by sequencing. It was verified that it is possible to mate sires and dams with different PRDM9 genotypes in order to try to increase genetic variability in buffalo populations, improving the matings choices in buffalo breeding, helping to maintain production levels.